VISUAL ENTITY OBJECT DETECTION SYSTEM IN SOCCER MATCHES BASED ON VARIOUS YOLO ARCHITECTURE - Althaf Pramasetya Perkasa, Mochamad; El Akbar, R. Reza; Al Husaini, Muhammad; Rizal, Randi (Informatika, Universitas Jenderal Soedirman, 2024)
In this study, a performance comparison between the YOLOv7, YOLOv8, and YOLOv9 models in identifying objects in soccer matches is conducted. Parameter adjustments based on GPU storage capacity were also evaluated. The results show that YOLOv8 performs better, with higher precision, recall, and F1-score values, especially in the